The Impact of IFRS 16 On the Financials of The Greek Listed Companies - Gerasimos Rompotis; Dimitris Balios (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- What was the impact of the adoption of the new international accounting standards for leases IFRS 16 on the financial statements of the Greek companies that are listed on Athens Exchange? Motivation- The majority of the relevant literature worldwide has examined the effect of IFRS 16 ex-ante, that is, before the actual implementation of the new standard. In addition, a relevant study for Greece, which stands as a developing regional economy, is missing. Our study seeks to fill this gap in the literature, as it is one of the few that have been conducted with actual data and, to the best of our knowledge, it is the first to focus on Greece. Idea- The impact of IFRS 16 was expected to be significant at several levels. This study examines the magnitude of the impact on the Greek companies of public interest. Data- Fist, we gather the financial statements of a sample of 79 Greek companies. Then, we compare several items of the financial statements for years 2018 and 2019, i.e., the year before the application of IFRS 16 and the year that the new standard was initiated. Tools- Based on the data found in the published financial statements for years 2018 and 2019, we measure the impact on key figures such as assets, liabilities, depreciation and interest expenses. Then, we assess the impact of IFRS 16 on several profitability, liquidity and leverage ratios. The significance of the impact on the financial ratios is also assessed with a single-factor cross-sectional regression analysis. Findings- Our findings indicate that key balance sheet figures, such as assets and total leasing liabilities, and significant profit and loss items, such as depreciation and interest expenses, are increased in 2019 compared to the previous year. The impact of the new standard on primary financial ratios was also substantial. Several ratios, such as EBITDA, ROE, ROA, ROCE, current ratio, leverage ratio and interest coverage ratio seem to have been affected by the new international accounting standard, to a less or a higher degree. A significant degree of consistency in financial ratios between 2018 and 2019 is also revealed. Contribution- Most of the studies on the subject conducted to date are mainly ex-ante evaluations of how the new standard would affect the financial position of the companies applying the IFRS accounting framework. Our paper stands as one of the few ex-post studies on the subject using data from financial statements that have been prepared following the requirements of IFRS 16. Therefore, in our study, the impact of IFRS 16 is no longer gauzed but it is actually measured with real data. In addition, our study is the first one for Greece, whose stock exchange is considered to be an advanced emerging market.
Keywords: M41; 650; Accounting standards; IFRS 16; operating leasing; financial leasing